Prevalence of Celiac Disease in Type 1 Diabetes Mellitus Children: A review of literatures in the Islamic Republic of Iran - Daniel Zamanfar; Mohsen Aarabi; Iman Sadeghian (Journal of Pediatrics Review, 2014)
Type 1 Diabetes Mellitus (T1DM) is the most chronic metabolic disorder in children. Celiac disease or gluten-sensitive enteropathy is a genetic and autoimmune disease which results from immune reaction to gluten. Therefore like type 1 diabetes mellitus, celiac disease is triggered by an environmental exposure in genetically susceptible individuals. The aim of this study was to review the articles reporting the prevalence of celiac disease in patients with type 1 diabetes in Iran. The results can be used for comparison with other countries, and also emphasizes the importance of screening for this disease in these patients. In this study, the articles published in PubMed, Google Scholar, Scientific Information Database (SID), Magiran and Iranmedex databases were reviewed. Three published studies (1 cross-sectional and 2 case-control) had been found and described the prevalence of celiac disease in patients aged 2-18 years with type 1 diabetes in Iran. The reported prevalence was between 3.4% and 6.8%. This is similar to reports from other countries however more studies are warranted.